The Pizarro-Almagro rivalry according to the General History of Peru: conquering mentality vs. literary heroism (Revista de Crítica Literaria Latinoamericana, 2017)
This study shows the internal tensions of Inca Garcilaso’s text in relation to the two central figures of the Conquest, Pizarro and Almagro. If he insistently affirms their heroic equality, the Inca’s account of the facts denies in part this equality and affirms his preference for Pizarro, inserting the two characters into the fatal mechanism of an inevitable tragedy.
Keywords: Conquest; Francisco Pizarro; Hernando Pizarro; Diego de Almagro; civil wars